SURFACE QUALITY OF PERUVIAN AMAZON WOODS SUBMITTED FOR PLANNING AND SANDING - Cárdenas, Miguel Meléndez; Juizo, Claudio Gumane Francisco; Guillén, Neptalí Bustamante; Mora, Hector Enrique Gonzáles; Klitzke, Ricardo Jorge; Da rocha, Márcio Pereira (Floresta, 2019)
The present study aimed to evaluate the quality of the machined surface of wood of Peruvian Amazonian species under industrial processing conditions. For this, planks of capirona (Calycophyllum spruceanum), cachimbo (Cariniana domestica) and copaíba (Copaifera paupera) were obtained from which four specimens of each species were removed and selected. The specimens were previously conditioned and subsequently submitted to planing and sanding operations, considering three cutting orientations (tangential, radial and intermediate). Then, the quality of the flattened and sanded surfaces of the studied species was evaluated by measuring the surface roughness (Ra) by means of a digital needle detection roughness meter. The results indicated significant differences in wood surface quality among the species in the three evaluated cutting planes, and the capirona radial plane had better planing and sanding quality. Concomitantly, due to the operations performed, the capirona wood allowed a greater possibility for better finishing, followed by cachimbo and copaíba wood, thus being grouped in the 1st, 2nd, and 3rd surface quality classes, respectively.